Repurposing Mobile-Assisted Language Learning (MALL) at Tourism Vocational Schools: Analysis of Group Dynamics and Technical Barriers in the "Tour-Vlog" Project - Baiq Husnia Hamidayani; M. Ragil Dwifani Azzura; Siti Mukminatun (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study explores the implementation of a Mobile-Assisted Language Learning (MALL)-based Project-Based Learning (PjBL) innovation through an English "Tour-Vlog" project. The focus of this research is directed at addressing the issues of passive learning and the counterproductive utilization of smartphones in the 11th-grade Tourism Services (Usaha Layanan Wisata/ULW) class at SMKN 2 Selong. Employing an exploratory mixed-methods case study design, data were gathered from 23 students through classroom observations, semi-structured interviews, perception questionnaires, as well as individual performance and group product assessment rubrics. Student speaking ability data in the individual performance assessment rubric was adapted from the components of Harris' (1969) standard oral test, which included aspects of fluency, pronunciation, grammar, and vocabulary adapted to the vocational context of tourism. The results demonstrate a significant transformation in the learning culture, shifting from passive detachment to active engagement, which achieved a 100% speaking participation rate. Furthermore, students exhibited highly positive perceptions regarding vocational career relevance (mean score of 4.61/5). Nevertheless, the success of the final group products remained varied, with only a 50% passing rate. Qualitative analysis revealed that this sub-optimal outcome was triggered by the phenomenon of social loafing within group dynamics and technical constraints, specifically environmental acoustic disturbances during outdoor recording processes. This study concludes that while integrating MALL into PjBL effectively mitigates students' speaking anxiety, it requires a stringent individual accountability mechanism to optimize collaborative learning outcomes in vocational contexts.